Translation Policy, Social System, and Ideology: A Study on the English Translation of Modern Chinese Fiction for America During the CWRAJ - Ping Li; Chuanmao Tian (SAGE Open, 2021)
This article explores translation policy on the English translations of modern Chinese fiction to American readers during China’s War of Resistance against Japan (1931–1945). The research findings show that translation policy may not be explicitly stated, but implicitly embodied in some political, diplomatic, and cultural policies made by the American and Chinese governments. Translation policy making as a social system is influenced by the political environment during the war. Different policy makers’ motives and policies change over time in reaction to each other with the course of the war, and the changing socio-political climate in China and the US had great effects on the English translations of Chinese fiction before the entry of the US into the war and after the US government became actively involved in translation projects. Moreover, the ideological preferences and political interests of the various actors shape actual translation practice—the selection of texts and actual choices in wording. This course of events affects the reception of these translations by the US public. In other words, the readership of these books grew after the Chinese government became allies in the war with the American government.